LENGTH WEIGHT RELATIONSHIP IN THE THREADFIN-BREAM, NEMIPTERUS JAPONICUS ALONG THE KERALA COAST - Vinci, G K; Nair, A K Kesavan (Indian Journal of Fisheries, 2011)
The length-weight relationship in N. japonicus of the Kerala coast shows no change in the form of the relationship when classified according to maturity and sex. The t-test shows that the cubic law does not hold good for this species. Instances of more than one value of weight for a given value of length are found more frequently in females than in males. A comparison of the relationships for the Andhra-Orissa coasts with those of the Kerala coast gives some differences which probably signify that separate stocks may exist in the Bay of Bengal and the Arabian Sea